Зрушення функціонального стану про- і антиоксидантної систем у міокарді, що виникли при пневмонії на тлі адреналінового пошкодження міокарду та їх корекція корвітином - Бородач, В.О.; Регеда, М.С. (Медична гідрологія та реабілітація, 2010)
В работе нами изучено состояние прооксидантной и антиоксидантной систем в миокарде морских свинок с экспериментальной пневмонией (ЭП) на фоне адреналинового повреждения миокарда (АПМ) в динамике (на первые, седьмые и четырнадцатые сутки) до и после лечения корвитином. Нами установлено, что при ЭП на фоне АПМ повышается накопление продуктов ПОЛ и снижается активность сеперосиддисмутазы (СОД) и каталазы (КТ) в миокарде животных, особенно на 7-е и 14-е сутки, а применение корвитина вызывает снижение уровня диеновых конъюгатов (ДК) и малонового диальдегида (МДА) и повышение активности СОД и КТ, что свидетельствует о корригирующем влияние этого препарата на нарушенные метаболические процессы. Pro- and antioxidant myocardium systems functional condition shifts arising in case of pneumonia in the background of the myocardium adrenaline damage and their treatment with corvitin. We have examined the pro-oxidant and antioxidant systems condition of Guinea pigs myocardium with experimental pneumonia in the background of myocardium adrenaline damage in dynamics (on the 1th, 7th and 14th days) before and after in treatment with corvitin. We have found out that the functional ability of the antioxidant system enzymes decreases, but at the same time the increase of lipid peroxidation processes is observed under the circumstances of experimental pneumonia in the background of myocardium adrenaline damage. The usage of corvityn has led to the decrease in diene conjugate and malondialdehyde contents and increase in superoxid